Digital Revolution and Means of E-Money Circulation (Trinity Journal of Management, IT & Media (TJMITM), 2017)
We can call digital revolution as serendipity which has changed  the whole concept of technology from what it was 10 years back.  Knowingly or unknowingly, many prodigious discoveries have  been made which has positively contributed towards the  advancements of the society that we live in. Not trite but original,  at times detrimental but mostly constructive, not frivolous but  vigorous, this also defines indomitability of digital revolution. In  contemplation, I had an epiphany that the preponderance of  Demonetization has changed the whole structure of the market.  There are myriad of questions brimming in the mind of Indian  citizens. Enough we have heard about the positive and negative  aspect of it but did we ever pause and think what exactly it has  given to our society? It has brought our society to a whole new  digital world. I can indubitably say that the catalytic impact on the  development of a “cashless economy” will hasten broader  governmental efforts to reduce tax evasion and black market  transaction. Introduction of newest substitute of traditional  payment method i.e. E-money has now become a part of the  monetary aggregates from the balance sheet of central banks.  The movement towards a global economy, merging operational  boundaries & unprecedented explosion of free trade/exchange  worldwide has brought about massive opportunities to develop  newer tools, instruments and methodologies in the fields of  strategic management & entrepreneurship. With the introduction  of E-money the operational policies, the regulatory system, the  degree of integration in the global economic and financial  markets and procedures of many organizations has radically  changed in order to give lucrative results.
Keywords: E-money; monetary statistics; monetary policy; substitute of traditional payment; cashless; digital; black money; network society; digital currency